2005
DOI: 10.1111/j.1532-950x.2005.00062.x
|View full text |Cite
|
Sign up to set email alerts
|

Use of Autogenous Fascia Lata Graft for Perineal Herniorrhaphy in Dogs

Abstract: FLG can be used without major complications for primary repair of PH, as an augmentation procedure when the internal obturator muscle is thin or friable, or when herniation has recurred after another repair technique.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
55
0
44

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(101 citation statements)
references
References 36 publications
1
55
0
44
Order By: Relevance
“…Cães inteiros apresentam uma taxa de recorrência 2,7 vezes superior à dos cães castrados (MORTARI; RAHAL, 2005), sendo que receptores para hormônios androgênicos estão presentes na musculatura do diafragma pélvico, e o aumento de di-hidrotestosterona circulante possa levar a atrofia deste (ACAUI, 2001). Embora essa indicação de tratamento seja comprovada, é possível verificar cães machos operados de hérnia perineal, não castrados (BONGARTZ et al;2005). Os animais desse estudo foram orquiectomizados, pois esse procedimento diminui o índice de recidiva pós-operatório (ANDERSON et al, 1998;HOSGOOD et al, 1995), Em um trabalho realizado por D'Assis e colaboradores (2010) foi observado hipertrofia prostática em cães com hérnia perineal, justificando o emprego da orquiectomia associado a herniorrafia perineal.…”
Section: Discussionunclassified
“…Cães inteiros apresentam uma taxa de recorrência 2,7 vezes superior à dos cães castrados (MORTARI; RAHAL, 2005), sendo que receptores para hormônios androgênicos estão presentes na musculatura do diafragma pélvico, e o aumento de di-hidrotestosterona circulante possa levar a atrofia deste (ACAUI, 2001). Embora essa indicação de tratamento seja comprovada, é possível verificar cães machos operados de hérnia perineal, não castrados (BONGARTZ et al;2005). Os animais desse estudo foram orquiectomizados, pois esse procedimento diminui o índice de recidiva pós-operatório (ANDERSON et al, 1998;HOSGOOD et al, 1995), Em um trabalho realizado por D'Assis e colaboradores (2010) foi observado hipertrofia prostática em cães com hérnia perineal, justificando o emprego da orquiectomia associado a herniorrafia perineal.…”
Section: Discussionunclassified
“…There are many different techniques of perineal hernia repair, of which the two most widely accepted are anatomical reduction technique which was performed in this case and internal obturator trauma. Closure of the hernia defect by transposition of the superficial gluteal muscle (Spreull and Frankland, 1980), semitendinosus muscle (Chambers and Rawlings, 1991) and fascialata (Bongartz et al, 2005) has been reported by various surgeons. Similarly synthetic materials like polypropylene mesh have also been used successfully for repair of perineal hernia in dogs (Szabo et al, 2007).…”
Section: Treatment and Discussionmentioning
confidence: 99%
“…Rectal prolapse can also occur after repair of perineal hernias because of tenesmus, especially in dogs with bilateral hernia, complicated by rectal sacculation 5,12 . Bongartz et al 7 reported 2 rectal prolapse in 12 dogs; they thought that simultaneous bilateral procedures might induce more pain, and stricture of the pelvic diaphragm lead to an increased effort during defecation. In the present study, both unilateral and bilateral perineal hernia were treated at the same operation, there were no severe pain inducing persistent tenesmus, and no prolapse recorded associated with pain.…”
Section: 610mentioning
confidence: 99%
“…Perineal hernia is characterized by disruption of the middle-aged or aged intact male dogs [1][2][3][4][5][6][7] . Approximately pelvic diaphragm and herniation of the abdominal or 59% of the perineal hernias are unilateral while 41% are pelvic organs into the ischiorectal fossa especially in bilateral 6 .…”
Section: Introductionmentioning
confidence: 99%